2019
DOI: 10.3389/fphar.2019.00385
|View full text |Cite
|
Sign up to set email alerts
|

DNMT Inhibitors Increase Methylation in the Cancer Genome

Abstract: DNA methyltransferase inhibitors (DNMTi) decitabine and azacytidine are approved therapies for myelodysplastic syndrome and acute myeloid leukemia, and their combinations with other anticancer agents are being tested as therapeutic options for multiple solid cancers such as colon, ovarian, and lung cancer. However, the current therapeutic challenges of DNMTis include development of resistance, severe side effects and no or partial treatment responses, as observed in more than half of the patients. Therefore, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 43 publications
1
54
0
1
Order By: Relevance
“…This makes them attractive targets for cancer therapy or chemoprevention (89). Indeed, several studies have demonstrated that TSG expression could be restored after treatment of cells with demethylating agents, and DNMT inhibitors, such as azacytidine and decitabine, are currently under preclinical and clinical investigations in various cancer types (e.g., ClinicalTrials.gov Identifier: NCT01193517, NCT03666559, and NCT04187703) (90)(91)(92)(93). Nonetheless, up until now, very limited data have been shown concerning the effectiveness of DNMT inhibitors in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…This makes them attractive targets for cancer therapy or chemoprevention (89). Indeed, several studies have demonstrated that TSG expression could be restored after treatment of cells with demethylating agents, and DNMT inhibitors, such as azacytidine and decitabine, are currently under preclinical and clinical investigations in various cancer types (e.g., ClinicalTrials.gov Identifier: NCT01193517, NCT03666559, and NCT04187703) (90)(91)(92)(93). Nonetheless, up until now, very limited data have been shown concerning the effectiveness of DNMT inhibitors in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Using DNA isolated from the same stem cells experiment as Figure 3, we show that while partial methylation (~ 50% at most CpG sites) could be seen in the DMSO control, it was not decreased upon treatment with 1μm DAC, and if anything the methylation increased ( Figure S1). While this is not unprecedented--DAC has been shown to increase methylation in some genomic locations [28] --it suggests that the epigenetic control point in the genome is unknown. We also cannot rule out the possibility that another epigenetically-regulated transcription factor in turn controls NRG1 type III expression; however from the microarray expression data none of the most up-regulated genes after DAC treatment were transcription factors ( Table 2) so this explanation appears less likely.…”
Section: Resultsmentioning
confidence: 99%
“…The 5AzadC treatment, for the monotherapy and combination groups, was carried out for three weeks to avoid potential adverse effects. 12 In contrast, all animals treated with SAM in the monotherapy and the combination setting received SAM daily via oral gavage from the start of treatment until the experimental end-point was reached. Our results show that all animals in the control group developed tumours that continued to grow until the experimental end-point at week 10 after tumour cell injection ( Figure 2B; Appendix S1: Figure S2).…”
Section: Effect Of Sam + 5azadc Combination On Mda-mb-231 Xenograftmentioning
confidence: 99%